Georgia : Report on the Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2003)
This report provides an assessment of fiscal transparency practices in Georgia against the requirements of the IMF Code of Good Practices on Fiscal Transparency. The assessment has two parts. The first part is a description of practice, prepared by the IMF staff on the basis of discussions with the authorities and their responses to the fiscal transparency questionnaire, and drawing on other available information. The second part is an IMF staff commentary on fiscal transparency in Georgia.